Emerging and well‐characterized chlamydial infections detected in a wide range of wild Australian birds. Issue 5 (25th January 2022) - Kasimov, Vasilli; Dong, Yalun; Shao, Renfu; Brunton, Aaron; Anstey, Susan I.; Hall, Clancy; Chalmers, Gareth; Conroy, Gabriel; Booth, Rosemary; Timms, Peter; Jelocnik, Martina
Abstract: Birds can act as successful long‐distance vectors and reservoirs for numerous zoonotic bacterial, parasitic and viral pathogens, which can be a concern given the interconnectedness of animal, human and environmental health. Examples of such avian pathogens are members of the genus Chlamydia . Presently, there is a lack of research investigating chlamydial infections in Australian wild and captive birds and the subsequent risks to humans and other animals. In our current study, we investigated the prevalence and genetic diversity of chlamydial organisms infecting wild birds from Queensland and the rate of co‐infections with beak and feather disease virus (BFDV). We screened 1114 samples collected from 564 different birds from 16 orders admitted to the Australia Zoo Wildlife Hospital from May 2019 to February 2021 for Chlamydia and BFDV. Utilizing species‐specific quantitative polymerase chain reaction (qPCR) assays, we revealed an overall Chlamydiaceae prevalence of 29.26% (165/564; 95% confidence interval (CI) 25.65–33.14), including 3.19% (18/564; 95% CI 2.03–4.99%) prevalence of the zoonotic Chlamydia psittaci . Chlamydiaceae co‐infection with BFDV was detected in 9.75% (55/564; 95% CI 7.57–12.48%) of the birds. Molecular characterization of the chlamydial 16S rRNA and omp A genes identified C. psittaci, in addition to novel and other genetically diverse Chlamydia species: avian Chlamydia abortus, Ca. Chlamydia ibidis and Chlamydia pneumoniae, all detected for the first time in Australia within a novel avian host range (crows, figbirds, herons, kookaburras, lapwings and shearwaters). This study shows that C. psittaci and other emerging Chlamydia species are prevalent in a wider range of avian hosts than previously anticipated, potentially increasing the risk of spill‐over to Australian wildlife, livestock and humans. Going forward, we need to further characterize C. psittaci and other emerging Chlamydia species to determine their exact genetic identity, potential reservoirs, and factors influencing infection spill‐over.